2013
DOI: 10.1186/1471-2334-13-49
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analyses of Fusarium isolates recovered from a cluster of invasive mold infections in a Brazilian hospital

Abstract: BackgroundInvasive fusariosis (IF) is a rare but often fatal fungal infection in immunosuppressed patients. In 2007, cases of IF above the expected epidemiologic baseline were detected in the hematology ward of a hospital in Rio de Janeiro, Brazil. Possible sources of infection were investigated by performing environmental sampling and patient isolate collection, followed by molecular typing. Isolates from dermatology patients with superficial fusariosis were included in the study for comparison to molecular t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 13 publications
2
54
2
4
Order By: Relevance
“…Although case series of Fusarium infections have been reported throughout the years (4,7,9,16,(20)(21)(22), only in a recent report was an indication of a potential correlation between MICs for Fusarium spp. and response to treatment found (22), where CLSI MICs for seven Fusarium isolates identified by molecular methods, antifungal therapy (voriconazole or both voriconazole and amphotericin B), and clinical response were documented for patients with invasive fusariosis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although case series of Fusarium infections have been reported throughout the years (4,7,9,16,(20)(21)(22), only in a recent report was an indication of a potential correlation between MICs for Fusarium spp. and response to treatment found (22), where CLSI MICs for seven Fusarium isolates identified by molecular methods, antifungal therapy (voriconazole or both voriconazole and amphotericin B), and clinical response were documented for patients with invasive fusariosis.…”
Section: Resultsmentioning
confidence: 99%
“…However, the perception is that new generic changes may be suggested, such as the establishment of the genus Bisifusarium to include the more commonly known members of the Fusarium dimerum SC and the name Neocosmospora solani to replace Fusarium solani (6). The most frequent causes of fungal infections are members of three complexes, the F. solani species complex (SC), the F. oxysporum SC, and the Fusarium (Gibberella) fujikuroi SC (which includes, among others, F. verticillioides and F. proliferatum), and the next most frequent causes belong to the F. dimerum SC and F. incarnatum-F. equiseti SC; their distribution could be region dependent (4,(7)(8)(9)(10). Common clinical presentations are onychomycosis, keratitis, allergic disease (sinusitis and bronchopulmonary disease) for nonimmunocompromised patients and disseminated disease, as well as other severe invasive infections, in immunocompromised hosts (e.g., patients with prolonged neutropenia and T-cell immunodeficiency) (1,4,(7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although, the distribution of Fusarium species varies globally, Fusarium solani, F. oxysporum and F. verticillioides are the most frequent causes of fusariosis (16,17). Molecular phylogenetic studies have revealed that this genus comprises species complexes and the majority of Fusarium isolates cannot be identified to the species level using traditional morphological methods (4).…”
Section: Introductionmentioning
confidence: 99%
“…An environmental investigation was carried out, which found Fusarium species in the hospital water and on the surface of water-related structures. However, molecular typing suggested a communitybased acquisition of infection because, while most clinical isolates were Fusarium solani, environmental isolates were predominantly Fusarium oxysporum (6).…”
mentioning
confidence: 99%